2022
DOI: 10.1038/s41467-022-29473-4
|View full text |Cite
|
Sign up to set email alerts
|

CDP-ribitol prodrug treatment ameliorates ISPD-deficient muscular dystrophy mouse model

Abstract: Ribitol-phosphate modification is crucial for the functional maturation of α-dystroglycan. Its dysfunction is associated with muscular dystrophy, cardiomyopathy, and central nervous system abnormalities; however, no effective treatments are currently available for diseases caused by ribitol-phosphate defects. In this study, we demonstrate that prodrug treatments can ameliorate muscular dystrophy caused by defects in isoprenoid synthase domain containing (ISPD), which encodes an enzyme that synthesizes CDP-ribi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Treatment of antisense oligonucleotide can prevent this pathogenic exon trapping and restore normal fukutin production on human primary myotube obtained from FCMD patients and from FCMD model mice knocked in the retro-transposal insertion [56]. CDP-ribitol prodrug ameliorates muscular dystrophy in mice that lack isoprenoid synthase domain-containing protein (ISPD), one of the causative genes of α-dystroglycanopathy [57]. Surprisingly, recent studies propose novel strategies toward brain malformation, despite the CNS and ocular anomalies begin to be formed during the first trimester in utero.…”
Section: Morphological Alteration Of Neuroblastoma Cells (Imr32) Afte...mentioning
confidence: 99%
“…Treatment of antisense oligonucleotide can prevent this pathogenic exon trapping and restore normal fukutin production on human primary myotube obtained from FCMD patients and from FCMD model mice knocked in the retro-transposal insertion [56]. CDP-ribitol prodrug ameliorates muscular dystrophy in mice that lack isoprenoid synthase domain-containing protein (ISPD), one of the causative genes of α-dystroglycanopathy [57]. Surprisingly, recent studies propose novel strategies toward brain malformation, despite the CNS and ocular anomalies begin to be formed during the first trimester in utero.…”
Section: Morphological Alteration Of Neuroblastoma Cells (Imr32) Afte...mentioning
confidence: 99%
“…Its extracellular subunit is modified with O -linked glycans, which is necessary for the proliferation of satellite cells. One study focused on ribitol-phosphate modification, which is necessary for functional maturation of α-dystroglycan ( Tokuoka et al, 2022 ). Cytidine-diphosphate (CDP-ribitol) is a donor substrate for ribitol-phosphate modification , and proof-of-concept work indicated that supplementation therapy with CDP-ribitol could accelerate development of therapeutic agents for diseases involving glycosylation defects, including DMD ( Tokuoka et al, 2022 ).…”
Section: Other Proteins Associated With the Notch Pathway: Megf10 And...mentioning
confidence: 99%
“…One study focused on ribitol-phosphate modification, which is necessary for functional maturation of α-dystroglycan ( Tokuoka et al, 2022 ). Cytidine-diphosphate (CDP-ribitol) is a donor substrate for ribitol-phosphate modification , and proof-of-concept work indicated that supplementation therapy with CDP-ribitol could accelerate development of therapeutic agents for diseases involving glycosylation defects, including DMD ( Tokuoka et al, 2022 ). These results suggest that modulations of Notch protein and pathway may be a promising therapeutic target for muscular dystrophies.…”
Section: Other Proteins Associated With the Notch Pathway: Megf10 And...mentioning
confidence: 99%
“…10,11 As matriglycan serves as a scaffold for the binding of various extracellular matrix (ECM) proteins, such as laminin, agrin, and perlecan, it is actively engaged in various cellular events such as muscle and brain development, 12,13 tumor mutagenesis, and pathogen infection. 14,15 Toward a better under-standing of the biological and correlated pathological events, which may lead to precise identification and potential interrogation of the disease process, 16 the construction of structure-defined matriglycan derivatives gained much research interest. 17,18 Recently, we developed a chemoenzymatic approach to assemble core M1, core M2, and core M3 O-mannosyl glycopeptides.…”
mentioning
confidence: 99%
“…The xyloglucosyl trisaccharide, α- d -Xyl p (1→3)-α- d -Xyl p (1→3)-β- d -Glc p -(1→)- l -Ser, is an important PTM in various proteins with regard to cell signaling, such as epidermal growth factor (EGF) domains of bovine blood-clotting factors, , protein Z, and notch receptors . Recently, matriglycan (Figure ), composed of a repetitive disaccharide unit with the alternative linkage of α-xylopyranoside and β-glucuronic acid [α- d -Xyl p- (1→3)-β- d -GlcA p -(1→3)-] n , is found as an extension of the core M3 O -mannosyl glycans on α-dystroglycan (α-DG), through the linkage of tandem repeating units of ribitol phosphates. , As matriglycan serves as a scaffold for the binding of various extracellular matrix (ECM) proteins, such as laminin, agrin, and perlecan, it is actively engaged in various cellular events such as muscle and brain development, , tumor mutagenesis, and pathogen infection. , Toward a better understanding of the biological and correlated pathological events, which may lead to precise identification and potential interrogation of the disease process, the construction of structure-defined matriglycan derivatives gained much research interest. , …”
mentioning
confidence: 99%